Recent detention of 11 proves IS threat becoming serious - New Sabah Times, English (KK) (New Sabah Times, 2015)
ALOR SETAR: The recent detention of 17 men, believed to be planning attacks on several locations in the country, was a clear indicator that the threat of the Iraq and Syria Islamic State (ISIS) in Malaysia had become more serious and dangerous.